FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN AKUNTANSI BERBASISIS AKRUAL PADA SKPD KABUPATEN SIDOARJO - Adirianto, Moh.; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to proof some factors which give influence to the implementation of accrual based accountancy at the local apparaturs work unit of Sidoarjo district. which consists of Human resources, organization commitment, organization culture, and accounting information system. This research applies quantitative method in which this method focuses on the hypothesis test. The research population is 24 local apparaturs work unit of Sidoarjo district. The data collection method has been done by using Purposive sampling. The data has been obtained by issuing questionnaires to the 75 employees of financial management at the local apparaturs work unit of Sidoarjo district. 73 (96%) questionnaires have returned and have been filled in completely and can be processed. The collected data has been processed by using multiple linear regressions analysis. The result of this research shows that variables i.e. human resources, organization culture, accounting information system give positive influence to the implementation level of accrual based accountancy. Unlike the previous variables, the organization commitment does not give any influence to the level of the implementation of accrual based accountancy. This indicates a variety of factors, such as inappropriate organizational policies, lack of awareness of employees in organization. Commitment can be realized if individuals exercise their right and obligations in accordance with their respective duties. Keywords: Human resources, organization commitment, organization culture, accounting information system, the Level of implementation of accounting accrual base.